PREVALENCE OF SERUM SUBOPTIMAL VITAMIN D3 LEVELS AND ITS CORRELATION WITH TREATMENT OUTCOME, SOCIODEMOGRAPHIC PROFILE AMONG CANCER PATIENTS: A RETROSPECTIVE ANALYSIS - BERA, ANJAN; DUTTA, SHATARUPA; BANERJEE, CHANDRIMA; BANERJEE, SAPTARSHI (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: In areas of etiology and prevention of cancer research, Vitamin D3 is currently one of the most promising agents. By virtue of anti-inflammatory, immunomodulatory, antiangiogenic, and proapoptotic effects, Vitamin D3 may inhibit carcinogenesis, cancer cell proliferation, and tumor progression. We wanted to study the prevalence of Vitamin D3 deficiency among cancer patients and whether there is any correlation between this Vitamin D3 level with response to the treatment of cancer and survival. Methods: Between, January 2014 and December 2017, 199 patients, who completed treatment at our radiotherapy department, were included in this study. In a non-fasting state, a venous blood sample was obtained during the follow-up period, and the serum level of Vitamin D3 was determined by chemiluminescence immunoassay method. Results: A higher prevalence of suboptimal D3 concentration was seen in patients with stable or progressive disease (PD) than in those patients cured, this was statistically significant. The complete response versus partial response and PD p-values are 0.0001 and 0.0008, respectively. Overall survival (OS) difference between D3 sufficiency and insufficiency is not statistically significant (p-0.4422). However, OS difference between D3 sufficiency and deficiency is statistically significant (p-0.0001). Similarly, the OS difference between D3 insufficiency and deficiency is statistically significant (p-0.0001). Conclusions: Vitamin D3 level is significantly associated with response and there is also a positive correlation with OS. Statistically significant (p-0.0001) OS difference between D3 insufficiency and deficiency is present. Statistically significant higher prevalence of suboptimal D3 concentration was seen in patients with stable or PD than in those patients cured.